The Analisis Pengaruh Arus Listrik Pada Proses Pengelasan Tig Terhadap Kekuatan Sambungan Las Material Logam Aluminium 6061 - Khalilullah, Ilham; Gunawan, Iwan; Siswanto, Ari (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Manufaktur Bandung (Polman Bandung), 2025)
The selection of current in aluminum welding has a significant impact on the quality of the weld joint. Too high a current can cause increased penetration, potential distortion and the risk of overmelting. On the other hand, too low a current can produce a weak weld joint, lack of penetration, and increase the risk of porosity formation. The main focus of this study is to understand the effect of current variations in the Tungsten Inert Gas (TIG) welding process on the strength of 6 mm thick aluminum 6061 welds and using ER4043 filler. The tensile strength and flexibility of the weld joint are very important in construction because they determine the strength, stability, and toughness of the joint to withstand static loads. This study shows that a welding current of 160 Ampere produces the highest tensile strength with an average value of 207.49 MPa, while a current of 100 Ampere has the lowest tensile strength with an average of 132.85 MPa. For a current of 130 Ampere, the average tensile strength was recorded at 154.128 MPa. The bending test results revealed that only welding with a current of 160 Ampere met the standard criteria, while currents of 100 Ampere and 130 Ampere experienced cracks and fractures that exceeded the standard limits. Microstructural analysis showed that in the heat affected zone (HAZ), the Mg2Si phase was most dominant at a current of 160 Ampere, which also applied to the weld metal. This Mg2Si phase contributed to the increase in the mechanical strength of the material. Based on these results, this study emphasizes the importance of choosing the right current in welding aluminum 6061, with a current of 160 Ampere as the best choice to produce strong weld joints.